The social representation of the woman about the cancer: implications for the nursing care - de Lima, Roberta (Online Brazilian Journal of Nursing, 2004)
The object of this research is the social representation of the cancer in the women with the breast cancer diagnosis and its implications in the nursing care. The theoretical reference is the social representation, according to Serge Moscovici. The objectives were characterize the social representation of the women about the cancer; analyze the implications of these representations in the care of their body and in their personal and social life and discuss the implications of these representations in the participation of the woman in her treatment and in the nursing care.The subjects were sixteen women that had the breast cancer diagnosis, matriculated in a public hospital . We utilized as collection data techniques the semi structured interview, the free association of ideas and the free observation. The data were organized in three categories: 1)the disease: the cancer and its metaphors; 2)the body and its psychosocial marks; 3) the care and its slopes. The results evidenced that the social representation of the cancer is still the one of an incurable disease, the one that affects the psychological scope, familiar and social of the woman. We concluded that the expressive slope of the care, evidenced in the relation established between the nurse and the client, is a useful way for the promotion of the well-being to the woman that, before needing of atechnical/technological arsenal needed to his treatment and cure, needs of an space that permits flowall the subjective load that mark the process of making sick, making possible more individualized care and the attention to the needs of psychosocial seal.